Business Transformation, Development of Human Resources Knowledge as The Key to Sustainability of Family MSME Businesses - Honorata Ratnawati Dwi Putranti; Sri Suyati; Adison Adrianus Sihombing; Mohamed Salah Elsayed Shalabi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Business transformation and development training are key determining elements in inviting family MSME businesses, especially in the context of increasingly tight business competition. This research aims to examine the impact of business transformation on desires through developing knowledge on the desires of family business MSMEs, by considering tacit and explicit factors. The research also investigates the moderating potential of the Human Resources (HR) knowledge development variable on business interest. The research results show that business transformation has a positive and significant influence on business continuity, and this influence occurs through the Human Recouse Knowlange Management (HRKM). However, the challenges and challenges faced by the MSME family. One of them is the limited amount of tacit knowledge possessed by the older generation, as well as the lack of financial support for training. Apart from that, complex government regulations also become obstacles in implementing transformation and training. Therefore, to achieve better outcomes in family businesses, it is important to address these challenges, either through better financial support, more effective tacit knowledge transfer, or simplification of government regulations. In this way, family MSMEs in the food sector can be better prepared to face increasingly fierce business competition and encourage their business aspirations.